Implementation Of Curriculum Management Of Tahfidz Al-Qur'an at Al-Qur'an Islamiyah Bandung Elementary School - Anwar, Cecep; Septiani, Dewi; Riva’i, Fuad Ahmad (STKIP Pesisir Selatan, 2024)
Qur'an memorization education has a significant role in shaping the character and morals of students. Elementary School (SD) Al-Qur'an Islamiyah Bandung is one of the educational institutions committed to integrating the tahfidz curriculum in daily learning. This study aims to analyze the implementation of the Qur'an tahfidz curriculum management at SD Al-Qur'an Islamiyah Bandung. The method used is a qualitative descriptive study with data collection techniques through interviews, observation, and documentation. The results showed that the management of the tahfidz curriculum in this school is carried out systematically, involving careful planning, interactive implementation, and periodic evaluation. The tahfidz teacher plays an important role in motivating students, while parental involvement increases learning support at home. The study concluded that the integration of tahfidz curriculum in general education at SD Al-Qur'an Islamiyah Bandung succeeded in creating a conducive learning environment for students in memorizing the Qur'an. Recommendations are given to improve teacher training and parental involvement in the learning process.